Validity, Reliability, and Application of the Session-RPE Method for Quantifying Training Loads during High Intensity Functional Training - Derek A. Crawford; Nicholas B. Drake; Michael J. Carper; Justin DeBlauw; Katie M. Heinrich (MDPI AG, 2018)
The session rate of perceived exertion method (sRPE) has often been utilized in sports activities in which quantification of external training loads is challenging. The multi-modal, constantly varied nature of high intensity functional training (HIFT) represents a significant hurdle to calculate external work and the sRPE method may provide an elegant solution to this problem. However, no studies have investigated the psychometric properties of sRPE within HIFT interventions. Twenty-five healthy men and women participated in six weeks of HIFT. Rate of perceived exertion and heart rate were assessed within every training session throughout the duration of the intervention. Compared to criterion heart rate-based measures, we observed sRPE method is a valid tool across individual, group, and sex levels. However, poor reliability in participants’ abilities to correctly match rate of perceived exertion with the relative level of physiologic effort (i.e., percentile of maximum heart rate) currently limits the utility of this strategy within HIFT. When applied, the validity and reliability of the sRPE seem to improve over time, and future research should continue to explore the potential of this monitoring strategy within HIFT interventions.